2014
DOI: 10.1007/s13224-014-0583-7
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Applicability of the Risk of Malignancy Index for Adnexal Masses to Patients Seen at a Tertiary Hospital in Chandigarh, India

Abstract: Back ground The discrimination between benign and malignant ovarian tumors is important considering to optimally plan for an appropriate surgical treatment. Aims To determine the applicability of risk of malignancy index (RMI 2) for triaging patients with adnexal masses seen at tertiary care hospital in India. Subjects and Methods A retrospective case note review of patients with adnexal masses admitted in Gynecology department was done. RMI 2 was calculated for each patient using ultrasound score, menopausal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Since 1990 with Jacobs’ suggestion to use RMI algorithms, several variations in RMI formula have been developed. Chopra et al [ 58 ] studied 100 patients, using a modified RMI with the maximum values for the U et M parameters were 4 instead of 3, which increased the sensitivity to 96.7% with 84% specificity, and a positive predictive value of 85.5%. Recently, the use of four different RMI formulas showed the same results for sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1990 with Jacobs’ suggestion to use RMI algorithms, several variations in RMI formula have been developed. Chopra et al [ 58 ] studied 100 patients, using a modified RMI with the maximum values for the U et M parameters were 4 instead of 3, which increased the sensitivity to 96.7% with 84% specificity, and a positive predictive value of 85.5%. Recently, the use of four different RMI formulas showed the same results for sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to develop more objective ultrasound-based approaches for discriminating between benign and malignant adnexal tumours. These include the risk of malignancy index (RMI), a scoring system based on menopausal status, a transvaginal ultrasound score and serum cancer antigen 125 (CA 125) level (Jacobs et al, 1990 RMI in classifying adnexal masses (Akturk et al, 2011;Al-Musalhi et al, 2015;Al Musalhi et al, 2016;Anton et al, 2012;Bouzari et al, 2011;Chacon et al, 2019;Chopra et al, 2015;Dochez et al, 2019;Hada et al, 2020;Javdekar & Maitra, 2015;Khoiwal et al, 2019;Meys et al, 2016;Westwood et al, 2018;Zhang et al, 2019). Three variants of the RMI (RMI-II, RMI-III, RMI-IV) have been developed, but these offer no significant additional diagnostic advantage compared with the original version (RMI-I) (Akturk et al, 2011;Hada et al, 2020;Meys et al, 2016;Zhang et al, 2019).…”
Section: Risk Of Malignancy Index (Rmi) and Risk Of Ovarian Malignancy Algorithm (Roma)mentioning
confidence: 99%
“…These include the risk of malignancy index (RMI), a scoring system based on menopausal status, a transvaginal ultrasound score and serum cancer antigen 125 (CA 125) level 16 . Many studies have demonstrated the diagnostic performance of the RMI in classifying adnexal masses 11,[17][18][19][20][21][22][23][24][25][26][27][28][29] . Three variants of the RMI (RMI-II, RMI-III, RMI-IV) have been developed, but these offer no significant additional diagnostic advantage compared with the original version (RMI-I) 11,22,27,28 .…”
Section: Risk Of Malignancy Index (Rmi) and Risk Of Ovarian Malignancy Algorithm (Roma)mentioning
confidence: 99%